Progress of Solid‐state Electrolytes Used in Organic Secondary Batteries. Issue 2 (29th December 2021) - Wang, Shaolong; Lv, Jing; Wang, Xuehan; Cui, Haixia; Huang, Weiwei; Wang, Yanzhi
Abstract: Organic electrode materials (OEMs) have attracted intensive attention owing to their high energy density, diverse structures and environmental friendliness. Unfortunately, the easy dissolution of OEMs in the organic liquid electrolytes (OLEs) severely damages the cycle stability of batteries. There is a hidden danger of catching fire due to a lot of heat generated from overcharge of the batteries. Moreover, OLEs are liable to leak and unstable at high voltage. Using solid‐state electrolytes (SSEs) could effectively alleviate the above‐mentioned problems at some extent. However, SSEs still show some weaknesses, including the large impedance of electrolyte‐electrode interface (EEI) and low ion conductivity. In this review, the latest progress in the research of SSEs used in organic secondary batteries (OSBs) are summarized, with particularly focus on the ionic conductivity of SSEs, the combination of organic electrodes/solid‐state electrolytes, the optimization of EEI and the batteries cycle stability. Future directions for the development of OSBs are given from viewpoints of solid batteries. Abstract : Solid‐state electrolytes effectively improve the cycle stability and safety of the organic secondary batteries.